MULTIMEDIA DEVELOPMENT IN VOCABULARY LEARNING FOR ENGLISH LANGUAGE EDUCATION PROGRAM - Lia Agustina Damanik (Institut Pendidikan Tapanuli Selatan, 2020)
The development of technology meets the needs of new ways in teaching language. This study aims to identify the aspects of the multimedia appeal of learning developed; to find out the attractiveness of students in vocabulary learning by using multimedia; to develop vocabulary learning for English language education students by using multimedia. This study was conducted by using research and development study. The subjects of the study consisted of 28 students in English Language Education Program. The instruments were questionnaires, observation guidelines, and test. Data were analyzed by using descriptive statistical techniques. The results of this study are: (1) the quality of multimedia learning developed in terms of aspects of content, learning, display, and programming is good. By using a score range of 1 to 5, the content aspect shows an average score of 3.75, the learning aspect shows an average score of 3.71, the display aspect shows an average score of 3.87, and programming shows an average score of 3, 75; (2) the aspect of attraction shows that the multimedia learning developed is very interesting: twenty students showed very attractive product appeal, eight students showed attractive product appeal; and (3) the use of multimedia learning English vocabulary has a good impact on the students’ vocabulary learning: of 28 students, there were 27 students (95%) who completed vocabulary learning in English Language Education Program